Effects of decellularized extracellular matrix derived from Jagged1-treated human dental pulp stem cells on biological responses of stem cells isolated from apical papilla - Phothichailert, Suphalak; Nowwarote, Nunthawan; Fournier, Benjamin P.J.; Trachoo, Vorapat; Roytrakul, Sittiruk; Namangkalakul, Worachat; Osathanon, Thanaphum (Frontiers in Cell and Developmental Biology, 2022)
Objective: Indirect Jagged1 immobilization efficiently activates canonical Notch signaling in human dental pulp stem cells (hDPSCs). This study aimed to investigate the characteristic of the Jagged1-treated hDPSCs-derived decellularized extracellular matrix (dECM) and its biological activity on odonto/osteogenic differentiation of stem cells isolated from apical papilla (SCAPs). Methods: Bioinformatic database of Jagged1-treated hDPSCs was analyzed by NetworkAnalyst. hDPSCs seeded on Jagged1 immobilized surface were maintained with normal or osteogenic induction medium (OM) followed by decellularization procedure, dECM-N or dECM-OM, respectively. SCAPs were reseeded on each dECM with either normal medium or OM. Cell viability was determined by MTT assay. Characteristics of dECMs and SCAPs were evaluated by SEM, EDX, immunofluorescent staining and alcian blue staining. Mineralization was assessed by alizarin red S, Von Kossa, and alkaline phosphatase staining. Statistical significance was considered at p<0.05. Results: RNA-seq database revealed upregulation of several genes involved in ECM organization, ECM-receptor interaction, and focal adhesion in Jagged1-treated hDPSCs. Immobilized Jagged1 increased the osteogenesis of hDPSCs culture with OM. dECMs showed fibrillar-like network structure and maintained major ECM proteins, fibronectin and type I-collagen, as well as glycosaminoglycans. A decrease in calcium and phosphate components was observed in dECMs after the decellularized process. Cell viability on dECMs did not alter by 7 days. Cell attachment and f-actin cytoskeletal organization of SCAPs proliferated on Jagged1-treated dECMs were comparable to those of the control dECMs. SCAPs exhibited significantly higher mineralization on dECM-N in OM and markedly enhanced on dECM-OM with normal medium or OM conditions. Conclusion: Jagged1-treated hDPSCs-derived dECMs have biocompatible and increase odonto/osteogenic differentiation of SCAPs. The results suggested the potential of Jagged1 dECMs, which could be further developed into ECM scaffolds for application in regenerative medicine.